Mobile biometrics - Guo, Guodong; Wechsler, Harry, 1948- (Institution of Engineering and Technology, 2017)
This book is about the use of biometrics on mobile/smart phones. An integrated and informative analysis, this is a timely survey of the state of the art research and developments in this rapidly growing area.
Keywords: Biometric identification.; Computer security.; Mobile computing.; elektronické knihy; electronic books